The sources of lyrical conflict in Tsvetaeva’s later works: life and being antinomianism - Павлова, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
This article concerns the antinomic installation of everyday life and life in the later works by Marina Tsvetaeva. The author, referring to Tsvetaeva’s works, highlights the importance of conflict of everyday life and being and shows its «specific» semantic value in Tsvetaeva’s poetry. Antinomy of life and existence is modeled through the multiple ontological oppositions of «down – up», «earth – sky», «body – spirit» and others. The author proves that Tsvetaeva’s conflict between everyday life and existence can be solved. Firstly, the romantic mismatch of the world of the earth, associated with a lie, to the world of heaven, which is essentially the ultimate truth, lies in this conflict. Secondly, an important component of this conflict is the love line, which turns out to be a sort of psychological key to conflict of everyday life and existence.